Astaxanthin ameliorates cisplatin‐induced damage in normal human fibroblasts. Issue 3 (12th September 2019) - Yamaguchi, Momoho; Tomihara, Kei; Heshiki, Wataru; Sakurai, Kotaro; Sekido, Katsuhisa; Tachinami, Hidetake; Moniruzzaman, Rohan; Inoue, Sayaka; Fujiwara, Kumiko; Noguchi, Makoto
Abstract: Objective: Oral mucositis is a common adverse side effect of cancer chemotherapy. Its management is of vital importance during cancer treatment. Oxidative stress against normal cells, including epithelial and stromal cells, has been implicated in the pathogenesis of chemotherapy‐induced oral mucositis. Fibroblasts may play a major role in the repair of oral mucosal tissue after chemotherapy. Astaxanthin (AST), a natural xanthophyll carotenoid, has sparked interest because of its strong antioxidant and anti‐inflammatory properties. This study illustrates the protective effects of astaxanthin on normal fibroblasts damaged by chemotherapy. Methods: Human normal fibroblasts were exposed to cisplatin. The cells were then assessed for cell viability, apoptosis, production of reactive oxygen species, migratory activity, and expression of platelet‐derived growth factor receptors (PDGFRs) in the absence or presence of astaxanthin. Results: Astaxanthin protected fibroblasts from the side effects of cisplatin, such as reduction in cell viability, apoptotic cell death, generation of reactive oxygen species, reduction in migration activity, and reduced expression of PDGFRs. Conclusions: Our results indicate a broad range of protection from cisplatin damage in fibroblasts by astaxanthin, implying its possible use as a novel therapeutic agent against chemotherapy‐induced oral mucositis.